Indicators Identification For Developing Earthquake Risk Disaster Model For Roads - Mona ForalisaToyfur (International Conference on Coastal and Delta Areas, 2015)
Road network in Indonesia are exposed to various natural hazards, such as earthquakes, floods, landslides, volcanic eruptions etc. These disasters often cause damage to roads and bridges. Losses due to disasters caused by the damage of road infrastructures as well as socio-economic losses due to traffic disruption are compromising the development of the country. Risk assessment as one early stage of disaster risk management for road network are essential to the sustainability of the road network.. Risk assessment for roads are needed for analysis how to reduce potential damage and losses which may occur on future disaster. As resources are limited, priorities need to be identified in implementing risk reduction measure to the road infrastructure. This research limitation only risk assessment for road link. Risk assessment is needeed in order to provide adequate information for decision makers at the national and local level in prioritizing disaster mitigation works for road links.The risk assessment process is based on the determination of disaster risk index, calculated from a series of risk indicators, for each of road links within a road network.